Invading Mongols and the Preservation of Korean Traditions: The Monk Iryŏn and the Memorabilia of the Three Kingdoms. Issue 1 (2nd January 2017) - Grayson, James H.
Abstract: In the thirteenth century, when the Kingdom of Koryŏ—a state ancestral to modern Korea—was threatened culturally as well as politically by Mongol invasion and domination, a leading monk of that era, Iryŏn, undertook to record the folklore of the ancient period, the era of the so-called Three Kingdoms, and to compile it into a major work. This effort might now be called 'salvage folklore', but the way in which Iryŏn conducted his research and analysed his materials suggests that he should be regarded as Korea's first folklorist, and that his work, the Memorabilia of the Three Kingdoms, should be regarded as the earliest extant compendium of folkloric material from Korea.